Distribution and speciation of lead in model plant Arabidopsis thaliana by synchrotron radiation X‐ray fluorescence and absorption near edge structure spectrometry. (28th December 2013) - Shen, Yating
<x xml:space="preserve">Abstract</x> To obtain reliable in situ information on the distribution and speciation of Pb in plants with low Pb content, special attention needs to be paid to the synchrotron radiation based micro‐X‐ray fluorescence and micro‐X‐ray absorption near edge structure (μ‐XANES) spectrometry to avoid specious results in the chosen XRF region of interest and speciation linear combination fitting. First, an Arabidopsis thaliana shoot cultured in a Pb solution is analyzed to obtain two‐dimensional Pb distribution graphs, where an overlap of Pb, As, Se, and Br lines in synchrotron radiation based micro‐X‐ray fluorescence spectra is found. To avoid this overlap, (1)As K‐L3 and Pb L3‐M5, (2)As K‐M3, (3)Pb L2‐M4, (4)Se K‐L3, and (5)Br K‐M3 lines should be chosen in the region of interest. The Pb content in the seed coat, root, and stem are 48.2, 17.3, and 5.8 times higher, respectively, than in the leaf, while the Pb content in the seed coat, root, stem, and leaf increased 3458, 1241, 420, and 72 times, respectively, compared with the A. thaliana sample without a Pb solution soak. Second, Pb speciation of the same shoot is analyzed using μ‐XANES. It is important to define a combination fitting range because different possible Pb combinations can emerge using different ranges. Different speciations were found in the root[Pb(Ac)2 and PbSO4], stem[Pb(Ac)2 and Pb3(PO4)2], leaf[Pb(OH)2 and Pb5Cl(PO4)3], and seed coat[Pb3(PO4)2, Pb(OH)2, and PbCO3] between the fitting range of E0 − 20eV and E0 + 70eV. A more complete Pb XANES database with more references, especially organic Pb compounds, is needed. Copyright © 2013 John Wiley & Sons, Ltd.